Accuracy of Samsung Smartphone Integrated Pulse Oximetry Meets Full FDA Clearance Standards for Clinical Use. - Browne, Sara H. (medRxiv, 2021)
BACKGROUND: Pulse oximetry is used as an assessment tool to gauge the severity of COVID-19 infection and identify patients at risk of poor outcomes.(1,2,3,4) The pandemic highlights the need for accurate pulse oximetry, particularly at home, as infection rates increase in multiple global regions including the UK, USA and South Africa(5). Over 100 million Samsung smartphones containing dedicated biosensors (Maxim Integrated Inc, San Jose, CA) and preloaded Apps to perform pulse oximetry, are in use globally. We performed detailed in human hypoxia testing on the Samsung S9 smartphone to determine if this integrated hardware meets full FDA/ISO requirements for clinical pulse oximetry. METHODS: The accuracy of integrated pulse oximetry in the Samsung 9 smartphone during stable arterial oxygen saturations (SaO(2)) between 70% and 100% was evaluated in 12 healthy subjects. Inspired oxygen, nitrogen, and carbon dioxide partial pressures were monitored and adjusted via a partial rebreathing circuit to achieve stable target SaO(2) plateaus between 70% and 100%. Arterial blood samples were taken at each plateau and saturation measured on each blood sample using ABL-90FLEX blood gas analyzer. Bias, calculated from smartphone readings minus the corresponding arterial blood sample, was reported as root mean square deviation (RMSD). FINDINGS: The RMSD of the over 257 data points based on blood sample analysis obtained from 12 human volunteers tested was 2.6%. INTERPRETATION: Evaluation of the smartphone pulse oximeter performance is within requirements of <3.5% RMSD blood oxygen saturation (SpO(2)) value for FDA/ISO clearance for clinical pulse oximetry. This is the first report of smartphone derived pulse oximetry measurements that meet full FDA/ISO accuracy certification requirements. Both Samsung S9 and S10 contain the same integrated pulse oximeter, thus over 100 million smartphones in current global circulation could be used to obtain clinically accurate spot SpO(2) measurements to support at home assessment of COVID-19 patients.